Robust Adaptive Null Broadening Method Based on FDA-MIMO Radar - Zihang Ding; Junwei Xie; Bo Wang; Haowei Zhang (IEEE Access, 2020)
Beamforming plays an important role in the array radar anti-interference. However, the interference targets with fast speed may move out of the narrow null area of the beampattern. A null broadening method with robust adaptive beamforming for frequency diverse array (FDA)-multiple-input and multiple-output (MIMO) systems is proposed in this paper. The projection preprocessing and windowing functions are applied to obtain stable beampatterns. Then, a novel null broadening method based on the covariance matrix reconstruction is realized by setting artificial fluctuations around each actual jammer. Finally, a new convex optimization model is established and solved to estimate the desired steering vector. Numerical simulations results verify the effectiveness of the proposed method.